2022
DOI: 10.1177/13623613221108010
|View full text |Cite
|
Sign up to set email alerts
|

‘The key to this is not so much the technology. It’s the individual who is using the technology’: Perspectives on telehealth delivery for autistic adults during the COVID-19 pandemic

Abstract: The COVID-19 pandemic prompted a large-scale move to remote delivery of healthcare services. However, little research has directly explored telehealth experiences of autistic adults, a population strongly affected by health inequalities and care access barriers. This study sought telehealth experiences of 11 autistic adults (aged 27–67 years), seven family members/carers (aged 44–75) reporting about autistic people and six service providers. In-depth qualitative interviews were conducted with all participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…To our knowledge, our results are comparable to findings of four other studies that reported qualitative data from open response survey questionnaires 15 , 20 , 25 , 27 and in-depth interviews with members of the autistic community in Australia, 16 the United Kingdom, 29 and Sweden. 23 Similar to our study, others have reported a wide range of positive and negative effects of national lockdowns in everyday experiences of autistic groups in the United Kingdom, Belgium, the Netherlands, Sweden, Spain, Italy, the United States, and Australia during the first months of the COVID-19 lockdown.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To our knowledge, our results are comparable to findings of four other studies that reported qualitative data from open response survey questionnaires 15 , 20 , 25 , 27 and in-depth interviews with members of the autistic community in Australia, 16 the United Kingdom, 29 and Sweden. 23 Similar to our study, others have reported a wide range of positive and negative effects of national lockdowns in everyday experiences of autistic groups in the United Kingdom, Belgium, the Netherlands, Sweden, Spain, Italy, the United States, and Australia during the first months of the COVID-19 lockdown.…”
Section: Discussionsupporting
confidence: 88%
“… 15 Further, the rapid replacement of face-to-face services for online/telehealth represented a unique opportunity to improve services' reach and overdue adaptations to the needs of the autistic community. 18 , 29 However, there has been less research in relation to the implications of the pandemic in relation to the conduct of future research with the autistic adult population.…”
Section: Introductionmentioning
confidence: 99%
“…As a case in point, emerging evidence shows that access to autism‐related services was disrupted during the COVID‐19 pandemic across sectors including community services (Bal et al, 2021; Bhat, 2021; Maljaars et al, 2022), employment opportunities and the opportunity to work from home (Schall et al, 2021), services and mental health support for primary and secondary students (Hurwitz et al, 2022; Jeste et al, 2020; Monahan et al, 2021; Neece et al, 2020), and health services (Bhat, 2021; Chung, 2020; Drum et al, 2020; Jeste et al, 2020). Barriers to services included staffing shortages, closure of sites and service providers, inability to work from home (Desroches et al, 2022; Schall et al, 2021), lack of educational support, and barriers to telehealth as an accessible or effective service modality (Ali et al, 2022). Our ability to address these challenges is again hampered by siloed systems of data collection and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits associated with online health services for autistic adults have been described in recent literature. 39,40 Such benefits included reduced travel, improved comfort (avoiding crowded waiting rooms with sensory overload), and ease of communication. However, there are also several disadvantages associated with virtual delivery of supports and programs to autistic adults that should not be disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…Disadvantages include technology issues, environmental distractions, and reduced engagement. 24,39,40 Further, virtual delivery excludes those who may require support with technology and do not have this support available to them, as well as those who do not have the access to a computer, tablet, phone, or Internet. It is important to recognize that online delivery of mind fulness as well as other interventions may benefit some autistic people, but not all.…”
Section: Discussionmentioning
confidence: 99%